The effect of reduced application of herbicides and mechanical measures on the fresh above-ground mass of broadleaf weeds in the soybean crop - Krstić, Jovana (Acta herbologica, 2023)
In May 2020, the European Commission announced the strategy “Farm to Fork”, in which one of the aim is to reduce the use of pesticides by 50% by 2030. The adoption of band application of herbicides, combined with mechanical measures, may contribute to achieve this goal. The aim of the study was to determine whether reducing application of herbicides by applying 50% of the recommended label rates in combination with an inter-row cultivation can result in satisfactory weed control in soybean. In the experiment, pre-emergence and post-emergence herbicides were applied using the broadcast and band application of herbicides with and without inter-row cultivation. Inter-row cultivation was applied one week after the first and second post-emergence application. Herbicides were applied with a backpack sprayer with compressed CO2 nozzles TeeJet XR 11002 (for broadcast application) and TP 4002 E (for 25 cm wide band application), 200 L ha-1 of water and a pressure of 2 bar. Using the band application of herbicides with inter-row cultivation achieved a reduction in the above-ground frash mass of weeds. There were no statistically significant differences between individual band application treatments of herbicides compared to the broadcast application of herbicide treatments.